Global energy demand and 2-degree target, report 2014 - Crastan, Valentin (Springer International Publishing, 2014)
This report takes a neutral and independent point of view in attempting to show concrete ways to achieve the goal of reducing the CO2 emissions and limiting the global warming to the 2-degree target. It presents an overall picture spanning all key countries. In the report, the temporal evolution of the main parameters is given from 1970 to 2011 for all regions of the world and all G-20 countries, starting from the basic data, gross inland consumption. The parameters are then extrapolated to 2030, taking into account current trends, local factors and the requirements of the 2-degree climate target. An important basis is the structure of the current energy consumption and energy flows of all regions of the world and all G-20 countries, which is analyzed in the appendix in detail and reproduced as clearly as possible. The reports from climate science make it clear that with a greater level of warming, adaptation is the more expensive option. Compliance with the 2-degree climate target is a challenge, but not impossible. The book is intended not only for the scientific community but also for decision makers in government and industry.